The geeks of war - Edwards, John. ([S.l.] : Pentagon Press, 2007)
Wars are fought on the battlefield, but the technologies that enable 21st-century warfare are developed in research laboratories. Within the walls of corporate, government, and academic labs, researchers are probing the edges of science to uncover technologies that will make warfare more efficient-and more deadly. This book looks at the people behind the curtain, and at the next generation of tactical, information, communication, vehicular, biological, and crypto-graphic systems. Featuring in-depth interviews with the project directors and scientists performing this groundbreaking research, The Geeks of War also examines their scientific, political, patriotic,and financial motives, as well as the implications these technologies may have for the future.
Keywords: Military art and science--Technological innovations; Military art and science--Technological innovations; Military research; Military research; United States; United States